Hydrolysis of oil palm empty fruit bunch using dilute acid - Salleh, Shanti Faridah (2011)
Extensive research activities have been carried out to identify the best technology to convert biomass to bioethanol and other value added chemicals. This research focuses on the conversion of the hemicelluloses in the Oil Palm Empty Fruit Bunch (OPEFB) fibre to xylose via an acid hydrolysis reaction. The objectives of this study are to investigate a potential pre-treatment method prior to acid hydrolysis, to optimise the reaction conditions and operation modes of the reactor as well as to study the kinetics of the acid hydrolysis of OPEFB fibre in a batch reactor. A preliminary assessment on the composition of the OPEFB fibre was conducted using TGA analysis and the following composition of the fibre (% dry weight basis) was obtained: cellulose, 44.5%; hemicellulose 26.5%; lignin, 19.1%. Since OPEFB contains more than 70% cellulose and hemicelluloses in its fibre, it is an excellent feed sock of fermentable sugars for bioethanol production. However, the cellulose and hemicelluloses in the fibre must firstly be converted to fermentable sugars namely glucose and xylose. Consequently, a 1-litre batch reactor was fabricated and commissioned to convert lignocellulosic materials in the fibre to either glucose or xylose. The maximum temperature of the batch reactor was 140 oC, while the liquid solid ratio was between 20:1 and 30:1. In the preliminary screening of the best acid, three different types of acid were employed; sulphuric acid (H2SO4), hydrochloric acid (HCl) and acetic acid (CH3COOH). The catalyst-screening study was conducted at 100oC and at a liquid solid ratio of 25:1. Sulphuric acid showed the highest catalytic effect, followed by hydrochloric acid and acetic acid. Sulphuric acid was selected and applied for subsequent studies. The effect of ultrasonic pretreatment on dilute acid hydrolysis of OPEFB was also examined. The experiments were conducted at two temperatures; 100oC and 140oC. The results showed that the exposure of the OPEFB fibre to 20 kHz signal of ultrasonication power at different amplitudes had a marked effect on the efficiency of low temperature (100oC) acid hydrolysis based on the yield of xylose. However, no improvement on yield of xylose was observed for acid hydrolysis at 140oC. SEM analysis showed that OPEFB fibre undergone significant morphological changes due to the effect of ultrasonic pretreatment under different acid hydrolysis conditions. Optimisation studies were conducted under various conditions; temperatures (80 oC to 140 oC), acid concentrations (2%, 4% and 6%), and reaction times (15 min, 30 min, 60 min, 90 min, 120 min and 150 min). The results indicated that the effect of acid concentration on the conversion of xylose was significant at higher temperature. At temperatures higher than 120oC, acid hydrolysis of OPEFB fibre favoured lower acid concentration and longer reaction time (more than 60 minutes). At lower temperatures (below 120oC), higher acid concentration and shorter reaction time (less than 60 minutes) improved xylose production. The monomeric xylose present in the liquid phase is the key indicator of the extent of the reaction, thus it was used as the basis for the kinetics modelling analysis. Kinetics study on the dilute acid hydrolysis of OPEFB fibre revealed that the hydrolysis reaction is a first order irreversible reaction. Dilute acid hydrolysis reaction was analysed using kinetics models developed by Saeman. Kinetics constants for Saeman model were analysed using Arrhenius type expansion which includes activation energy and catalyst concentration factors. A general kinetics model for acid hydrolysis of OPEFB fibre in terms of acid concentration and temperature was then developed. This work highlighted the potential of OPEFB fibre as a feasible feed stock for production of fermentable sugars especially xylose for bioethanol production. This work also demonstrated the ability of the in-house batch reactor to convert OPEFB fibre to xylose with 80% conversion. The breakthrough of this research was the discovery of the ability of ultrasonic pretreatment to physically alter the surface of OPEFB fibre, hence increase the yield of xylose. Ultrasonication of biomass has the potential to be integrated with existing lignocelluloses pretreatment technologies in biomass to bioethanol production to enhance the overall conversion efficiency.